2013
DOI: 10.1371/journal.pone.0072201
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Carbon Storage and Its Distribution by Stand Age and Forest Type in Boreal and Temperate Forests in Northeastern China

Abstract: The northeastern forest region of China is an important component of total temperate and boreal forests in the northern hemisphere. But how carbon (C) pool size and distribution varies among tree, understory, forest floor and soil components, and across stand ages remains unclear. To address this knowledge gap, we selected three major temperate and two major boreal forest types in northeastern (NE) China. Within both forest zones, we focused on four stand age classes (young, mid-aged, mature and over-mature). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 40 publications
5
32
0
Order By: Relevance
“…The C stock of tree species correlates positively with BA, TD, diversity, and forest productivity (Baishya et al 2009;Borah et al 2015;Joshi and Dhyani 2018). Furthermore, the age of forest stand also influences the biomass and correlates positively with forest C stock in previous studies, indicating an increase in C storage with stand age (Wei et al 2013;Köhl et al 2017). The older stand age of these forests results in temporal net primary productivity (NPP) accumulation and increases the overall tree C storage (Chen et al 2016).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The C stock of tree species correlates positively with BA, TD, diversity, and forest productivity (Baishya et al 2009;Borah et al 2015;Joshi and Dhyani 2018). Furthermore, the age of forest stand also influences the biomass and correlates positively with forest C stock in previous studies, indicating an increase in C storage with stand age (Wei et al 2013;Köhl et al 2017). The older stand age of these forests results in temporal net primary productivity (NPP) accumulation and increases the overall tree C storage (Chen et al 2016).…”
Section: Discussionmentioning
confidence: 85%
“…The largest and very important C pool in the terrestrial ecosystem is SOM, which contains soil organic carbon (SOC) and plays a great role in the cycling of nutrients and C between the lithosphere and atmosphere (Lal 2005). C pools in various forest ecosystems are strongly influenced by temperature, rainfall, topography (Vayreda et al 2012), forest type and structure (Wei et al 2013), tree species composition (Hu et al 2015), species diversity (Arasa-Gisbert et al 2018), land use changes, and human-induced disturbances (Canadell et al 2007). An estimation of the existing pools of C in different forest types is hence required in order to make necessary management strategies related to C sequestration and storage (Johnson and Kern 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Boreal forests store approximately one-third of global terrestrial carbon and therefore are highly important in this context [3]. The carbon sequestration in forests is affected by climate [4], soil [5], and natural disturbance [6], along with forest stand characteristics, such as tree species composition [7], age [8,9], and silviculture practices [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these previous studies were mainly conducted on forest biomass C storage at the national and regional scales with different estimation methods and different forest resource data. Moreover, there are few precise studies concerning direct plot investigations for various forest types, C storage estimates that include understory, forest floor, and soil, and the relationship between climatic factors and forest types on regional scales [12][13][14][15][16]. An age-related study on C storage in a black locust forest ecosystem on the Loess Plateau showed that tree C storage increased from 5 to 38 years, but significantly decreased from 38 to 56 years owing to high tree mortality.…”
Section: Introductionmentioning
confidence: 99%